ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN UMKM KULINER DALAM MENDUKUNG INDUSTRI PARIWISATA NUSA DUA - Ni Luh Wulani Parwati; Putu Ratna Windusara Putri; I Made Sujana; Anak Agung Istri Setiari Jmh (Yayasan Nusantara Hasana Berdikari, 2022)
This study aims to analyze the factors influencing the success of culinary Micro, Small, and Medium Enterprises (MSMEs) in supporting the tourism industry in Nusa Dua, Bali. Culinary MSMEs play a strategic role in enhancing tourist destination attractiveness through food and beverage products that reflect local cultural identity. This research employed a quantitative approach using survey techniques involving culinary MSME owners in Nusa Dua. Data were analyzed through descriptive analysis and multiple linear regression. The findings indicate that product quality, menu innovation, service quality, digital marketing, and government support have positive and significant effects on the success of culinary MSMEs. Service quality emerged as the most dominant factor because tourists tend to evaluate their overall consumption experience when selecting culinary businesses. The results suggest that improving entrepreneurial competencies, utilizing digital technologies, and strengthening collaboration with the tourism sector are essential strategies for enhancing the competitiveness of culinary MSMEs in tourism destinations. This study is expected to provide valuable insights for local governments, business actors, and researchers in developing sustainable MSME sectors.